2020
DOI: 10.1001/jamaneurol.2019.3606
|View full text |Cite|
|
Sign up to set email alerts
|

Selective Vulnerability of the Nucleus Basalis of Meynert Among Neuropathologic Subtypes of Alzheimer Disease

Abstract: IMPORTANCE Corticolimbic patterns of neurofibrillary tangle (NFT) accumulation define neuropathologic subtypes of Alzheimer disease (AD), which underlie the clinical heterogeneity observed antemortem. The cholinergic system, which is the target of acetylcholinesterase inhibitor therapy, is selectively vulnerable in AD.OBJECTIVE To investigate the major source of cholinergic innervation, the nucleus basalis of Meynert (nbM), in order to determine whether there is differential involvement of NFT accumulation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 43 publications
4
87
3
Order By: Relevance
“…It is well established that cortical tau burden is associated with cognitive impairment in AD as indicated by human neuropathological [26] and in vivo tau PET binding [50] studies. This study also revealed that higher burden of quantified cortical tau burden is associated with earlier age at disease onset which is in agreement with a previous quantification neuropathological study [51] as well as a tau PET binding study in autosomal dominant AD [52] that indicated that increased tau PET uptake was linked to the onset of cognitive dysfunction. Although the presence of LATE-NC has been implicated as a clinical modifier of AD, we could not find a relationship between severity of LATE-NC with age at onset or rate of cognitive decline between AD/LATE-NC and AD cases, further supporting the notion that TDP-43 pathology does not impact disease onset or progression of AD.…”
Section: Discussionsupporting
confidence: 92%
“…It is well established that cortical tau burden is associated with cognitive impairment in AD as indicated by human neuropathological [26] and in vivo tau PET binding [50] studies. This study also revealed that higher burden of quantified cortical tau burden is associated with earlier age at disease onset which is in agreement with a previous quantification neuropathological study [51] as well as a tau PET binding study in autosomal dominant AD [52] that indicated that increased tau PET uptake was linked to the onset of cognitive dysfunction. Although the presence of LATE-NC has been implicated as a clinical modifier of AD, we could not find a relationship between severity of LATE-NC with age at onset or rate of cognitive decline between AD/LATE-NC and AD cases, further supporting the notion that TDP-43 pathology does not impact disease onset or progression of AD.…”
Section: Discussionsupporting
confidence: 92%
“…Herein, we have made use of thioflavin S as a fluorophore for the detection of NFTs of hyperphosphorylated tau protein. ThS is frequently used for the identification of NFTs in human brain tissue [7,14,17,24,25]. When stained with ThS, NFTs most notably produce characteristic flame-like morphologies in intraneuronal occlusions, distinctive from larger extracellular senile plaques that typically span tens of microns in diameter [26].…”
Section: Introductionmentioning
confidence: 99%
“…The nucleus basalis is rich in acetylcholine and stimulates the cholinergic system of the neocortex [44]. Neuronal loss in this region is thought to occur in the early stages of Alzheimer's disease [45][46][47]. It is reasonable to believe anticholinergic drugs could contribute towards neuronal loss in the nucleus basalis, as studies have identified that these neurons are susceptible to other toxic agents such as cadmium, aluminium, nitric oxide and ethanol [48][49][50].…”
Section: Discussionmentioning
confidence: 99%